Influenza B presenting as cardiogenic shock and progressing to multiorgan failure: A case report. (2022) - Murnaghan, Kyle; Alkharaza, Ahmad; Robbins, Mark; Haroon, Babar
Abstract: Influenza induced cardiogenic shock is rare and the majority of reported cases are a result of Influenza A myocarditis. We describe a patient with Influenza B who developed myocarditis and cardiogenic shock, with no known pre-existing heart disease. The patient's disease progressed to include rhabdomyolysis, compartment syndrome, renal failure, and pneumonia. He was successfully managed with Oseltamivir, renal replacement therapy, antimicrobials and intubation. This case is notable due to the rarity of influenza B induced cardiogenic shock and reinforces the importance of recognition and treatment.